2021
DOI: 10.3390/nu13082710
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Differences According to Ultra-Processed Food Consumption in a Spanish Population

Abstract: Ultra-processed foods (UPFs) consumption could affect gut microbiota diversity and profile. We aimed to evaluate the effects of UPFs on microbiota, considering the role of sex. The consumption of UPFs (using NOVA criteria) was assessed with a validated 137-item food-frequency questionnaire. Participants (n = 359) were classified into less than three servings per day (n = 96) of UPFs and more than five (n = 90). Women and men were subclassified following the same criteria. 16S rRNA sequencing was performed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 75 publications
2
60
0
1
Order By: Relevance
“…In the present study, the population was categorized according to tertiles of UPF consumption, and we observed that subjects allocated in the highest tertile presented lower adherence to MedDiet and higher total energy intake. These results were in line with the aforementioned articles, and very similar to the ones obtained previously by Cuevas-Sierra et al where higher values of total energy intake and a lower adherence to MedDiet were observed in subjects consuming more than 5 UPF servings/day (18).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the population was categorized according to tertiles of UPF consumption, and we observed that subjects allocated in the highest tertile presented lower adherence to MedDiet and higher total energy intake. These results were in line with the aforementioned articles, and very similar to the ones obtained previously by Cuevas-Sierra et al where higher values of total energy intake and a lower adherence to MedDiet were observed in subjects consuming more than 5 UPF servings/day (18).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, dietary fiber may increase peripheral insulin sensitivity through short-chain fatty acids produced by the gut microbiota and their capacity to ferment fiber [36,37]. Some studies also demonstrated that UPFs might directly modulate gut microbiota configuration, richness and diversity [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…UPF is similar to the Westernized diet from the point of energy and nutrition, being made from refined carbohydrates, fat, sugar, protein isolates and various additives. The Westernized diet and UPF could reduce gut microbiota diversity and lead to dysbiosis, which is a feature of IBD [ 11 , 12 ]. Hence, current studies aim to improve gut microbiota through diet strategies or food components in order to achieve IBD remission.…”
Section: Introductionmentioning
confidence: 99%